Morphological screens using aged primary adult neuronal, microglial, and astrocytic cultures to find novel neurotherapeutics - Sefiani, Arthur (Frontiers in Cellular Neuroscience, 2023)
The average age of a patient with neurotraumatic injuries or neurodegenerative diseases has been increasing worldwide. The preclinical live animal models used for neurotrauma and neurodegenerative diseases are typically young adults, failing to represent the age of humans in the clinic. This dichotomy in age between human populations and animal models is likely to impede the understanding of the pathological mechanisms of most neurological disorders and the translation of their respective promising therapies. This lack of cohesion between animal models and patients in the clinic begins prior to in vivo testing, it starts during the in vitro drug screening phase. Conventional screening methods typically involve the use of stem cell derived neural cells, with some researchers using embryonic derived neural cells instead. These cells lack the fundamental characteristics present in aged neural cells, such as age-induced changes in process length and branching in microglia and how astrocytes respond to various insults. Various technologies and techniques have been developed recently that can help researchers use age-appropriate neural cells for their drug discovery endeavors. The use of age-appropriate neural cells during screening phases is hypothesized to significantly increase the translation rate of the hits to the geriatric patients suffering from neurotraumatic and neurodegenerative diseases.